The right ventricle—the forgotten chamber that deserves more love - Nguyen-Truong, Michael, author; Wang, Zhijie, advisor; Chicco, Adam, committee member; Li, Yan Vivian, committee member; McGilvray, Kirk, committee member; Popat, Ketul, committee member (Colorado State University. Libraries, 2022)
Right ventricle failure (RVF) is associated with serious cardiac and pulmonary diseases that contribute significantly to the morbidity and mortality of patients. The prevalence of RVF is significantly increased in the later stages of pulmonary hypertension, congenital heart disease, and left heart failure with preserved ejection fraction. Moreover, the mortality rate of these patients has not improved with currently limited treatment options. The persistent clinical challenge is mainly due to an incomplete understanding of the structure-function relationships of the RV, partly attributed to the lack of large animal models, as well as the lack of RV-specific therapies. Therefore, the overall goal of the study is to fill knowledge gaps in the biomechanics of right ventricle failure secondary to pressure overload and in the regenerative potential of mesenchymal stromal cells (MSCs) regulated by RV mechanics. The specific aims are: 1. Assess the unique ex vivo biomechanics of the RV free wall in contrast to the LV free wall. 2. Assess the ex vivo biomechanics of the "significant other" of the RV chamber – the septum wall. 3. Establish a novel ovine model of RV failure and investigate RV biomechanical changes during RV failure progression. 4. Investigate the pro-angiogenic paracrine effect in the context of mesenchymal stromal cell mechanobiology to ultimately improve RV therapy. From ovine models, there was distinct anisotropic mechanical behavior of the RV compared to the left side in healthy adults, and the low-strain mechanical behavior was correlated to collagen III. Multiscale computational model indicated softer collagen fibers in the RV. The investigation on the septal wall originally revealed transmural biomechanical changes and a significantly more compliant wall than the ventricular free walls. A new adult RV failure was established, and there was stiffening of the RV in the outflow tract direction and altered tissue anisotropy with RV failure progression. Finally, from prior and our own RV mechanical data, biomimetic scaffolds that represent healthy and diseased RV mechanics were fabricated for the first time. The pro-angiogenic potentials of MSCs on these scaffolds were assessed by cytokine production and neovessel formation. There were synergistic effects of matrix stiffness and anisotropy on MSC pro-angiogenic functionality.